Biomonitoring of PFOA, PFOS and PFNA in human milk from Czech Republic, time trends and estimation of infant's daily intake - Černá, Milena; Grafnetterová, Anna Pinkr; Dvořáková, Darina; Pulkrabová, Jana; Malý, Marek; Janoš, Tomáš; Vodrážková, Nicole; Tupá, Zdeňka; Puklová, Vladimíra (Environmental research. Section A, 2020)
BACKGROUND: Perfluoralkylated substances (PFASs) are persistent and bioaccumulative environmental contaminants. They are included on the list of emergent compounds monitored in the frame of HBM4EU project. OBJECTIVES: To analyze PFASs levels in human milk samples collected in the period 2006 through 2017, to follow their time trends, to assess the PFASs exposure in breastfed infants, to calculate the daily intake of PFASs and to compare it with the tolerable daily/weekly) intakes and to quantify risk from exposure using the hazard quotient and hazard index approach. MATERIAL AND METHODS: A broad spectrum of PFASs were analyzed by means of UHPLC-MS/MS in primipara human milk samples collected in four consecutive time periods 2006, 2010/11, 2014, and 2017; N = 46, 183, 164 and 232, respectively. Mothers living in urban and suburban residences were recruited after their delivery at maternity hospitals, and milk samples were taken within 2 and 8 weeks after delivery. The questionnaire was focused on possible sources of exposure, dietary habits and lifestyle. RESULTS: Only perfluorooctane sulfonate (PFOS) and perfluorooctanoid acid PFOA (in 2017, also perfluorononanoic acid (PFNA)) were quantified in more than 90% of analyzed human milk samples. In all sampling periods, the levels of PFOA were higher than those of PFOS (p < 0.05). A significant downward temporal trend (p < 0.001) was observed for both PFOA and PFOS levels. The median concentrations in sampling years 2006, 2010/11, 2014, and 2017 were 0.075, 0.059, 0.035, and 0.023 ng/mL for PFOA and 0.045, 0.031, 0.029, and 0.020 ng/mL for PFOS, respectively. In 2017, PFNA was also quantified in 99% of samples with the median concentration of 0.007 ng/mL. The levels of PFASs correlated with maternal sea fish consumption. No maternal age-related relationship was observed. Using the tolerably daily intake (TDI) values for PFOS and PFOA set by the European Food Safety Authority (EFSA) in 2008, the calculated daily intakes from breastfeeding were clearly below these limits. Using the new, more conservative EFSA Provisional Tolerably Weekly Intake (PTWI) values set in 2018, we demonstrated a considerable exceedance of PTWI, with a hazard index above 1. CONCLUSION: Significant time-related decreasing trends in the PFOS and PFOA levels in human milk were observed. Nevertheless, the body burden of infants from breastfeeding might pose an enhanced health risk to infants when the current PTWI values are applied. These findings strongly support the present EU efforts to phase out PFOA, its salts and PFOA related compounds. Since PFOS exposure there has still been widely detected despite PFOS usage reduction measures, the major exposure routes should be further monitored and, if possible, eliminated.
Keywords: Animals; Biological Monitoring; Female; Infant; ženské pohlaví; Tandem Mass Spectrometry; kapryláty; mateřské mléko; lidé; těhotenství; Fluorocarbons; Humans; Milk, Human; tandemová hmotnostní spektrometrie; kojenec; Czech Republic; Environmental Pollutants; biologický monitoring; Alkanesulfonic Acids; Caprylates; kyseliny alkansulfonové; Česká republika; zvířata; látky znečišťující životní prostředí; Pregnancy; fluorokarbony